Prevalence of selected chronic diseases, health seeking behaviour and associated factors among the elderly workers of a selected district of Sri Lanka - Niluka Gunathilaka; Dulani L. Samaranayake; Manuj C. Weerasinghe (Journal of the College of Community Physicians)
Introduction: Sri Lankan demographic transition has shifted the country to a fast-ageing population. Consequently, elderly in labour force will be noteworthy. Ageing increases the prevalence of non-communicable diseases. Hence, its prevalence, health seeking behaviour and associated factors need to be sought to improve the health of elderly workforce. Objectives: To describe the sociodemographic and work-related characteristics of elderly workers, health status, health seeking behaviour and association between the health seeking behaviour and sociodemographic and work-related characteristics in Gampaha District of Sri Lanaka Methods: A community-based descriptive cross-sectional study was conducted using multistage cluster sampling in Gampaha District, Sri Lanka among 835 elderly workers who met the operational definition and eligibility criteria. Data were collected using a pretested interviewer-administered questionnaire, covering sociodemographic and occupational details, and information on chronic illnesses and health-seeking behaviour. Bivariate analysis was carried out using Chi--squared test, considering a p-value of 0.05 as statistically significant. Results: Majority of the workers (78.4%; n=655) were having at least one chronic illness and the occupation of 58% of them was affected by their chronic illness. For acute and chronic illness, 48.1% were taking treatment from private medical centres.  The healthcare seeking behaviour for chronic conditions among the elderly was influenced by factors such as educational level, income, marital status, living arrangements, skill level and working patterns. Conclusions & Recommendations: The findings emphasize the need for policies and interventions that address socio-demographic disparities in healthcare access by promoting family support, insurance schemes, and adopting the health care facility provision according to the workplaces and working patterns.